2007
DOI: 10.1021/ol7019857
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of Oxonium Ylide with Isatins:  Efficient and Stereoselective Construction of Adjacent Quaternary Carbon Centers

Abstract: The 3-substituted 3-hydroxyindolin-2-ones with adjacent quaternary stereocenters were constructed in a single step via an efficient and stereoselective trapping of oxonium ylide with isatins. This reaction proceeds well in supercritical CO2 and is an example of the ability to use green approaches to efficiently construct polyfunctional molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…Incorporating protecting groups on the N1 of oxindole had no effect on reactivity, and gave the desired product in almost quantitative yield (99%) ( Table 2, entry 16). However, the electronic properties of the substituents at the isatin affected the yields strongly ( Table 2, entries [17][18][19][20]. Isatin with an electrondonating group only gave 60% yield.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Incorporating protecting groups on the N1 of oxindole had no effect on reactivity, and gave the desired product in almost quantitative yield (99%) ( Table 2, entry 16). However, the electronic properties of the substituents at the isatin affected the yields strongly ( Table 2, entries [17][18][19][20]. Isatin with an electrondonating group only gave 60% yield.…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the significance of this structural motif, numerous elegant synthetic methodologies have been developed [13][14][15][16][17][18][19][20][21] and aim to facilitate the synthesis of sufficient quantities of the desired natural products and related analogues for biological evaluation and structure-activity relationship studies, and thus finally contribute to the development of new therapeutic agents or important biological tools. The most direct approach to 3-substituted-3-hydroxy oxindoles is a nucleophilic addition of appropriate nucleophiles to isatins, such as the aldol reaction or an alkylation of isatins.…”
Section: Figurementioning
confidence: 99%
“…Trapping intermediates II with aldehydes resulted in 4; the desired process was in competition with an irreversible intramolecular proton transfer within IIa/IIb leading to the OÀH insertion side products 5 (Scheme 1). We also observed that addition of a stoichiometric amount of the Lewis acid Ti(OtBu) 4 suppressed the OÀH insertion.…”
Section: IImentioning
confidence: 60%
“…[4c] The reaction was proposed to proceed through the alcoholic oxonium ylide intermediates IIa or IIb (Scheme 1), which are generated in situ from 1 and benzyl alcohol (2) in the presence of Rh 2 (OAc) 4 . Trapping intermediates II with aldehydes resulted in 4; the desired process was in competition with an irreversible intramolecular proton transfer within IIa/IIb leading to the OÀH insertion side products 5 (Scheme 1).…”
Section: IImentioning
confidence: 99%
See 1 more Smart Citation